Prenatal Diagnosis of Thalassemia - Sunarto Sunarto (Indonesian Pediatric Society, 1993)
Thalassemia is an individual as well as a community health problem in some countries. It causes a lifelong suffering for the affected individuals. There is no treatment other than supportive, i.e. regular transfusions and removal of iron overload from the body. Only by such continuous and expensive treatment thalassemic patients can-generally achieve nearly normal health, but the health burden of such therapy for a large number of thalassemic patients is unaffordable by the affected communities. Prevention of the births of thalassemic babies is the choice for controlling the thalassemia and has been successful in many countries. For this purpose reliable and time accurate prenatal diagnosis is a conditio sine qua non. Blood fetal sampling is safe and can be done after 16 weeks gestation, amniocentesis after 14 weeks, and even chorionic villi sampling as early as 8 weeks gestation. In vitro globin synthesis analysis applied to the fetal blood sample is very reliable to measure the rate of synthesis of the globin chains that make up the hemoglobin. The-DNA analysis of the fibroblasts obtained by amniocentesis or of the chorionic villus sample is very sensitive and specific for the diagnosis of the genetic disorder in thalassemias. By involving the prenatal diagnosis, the birth of B-homozygous thalassemia has decreased by up to 90%.